Pengaruh Model Pembelajaran Treffinger Terhadap Higher Order Thinking Skills Peserta Didik Kelas V Sekolah Dasar - Izzatika, Amrina; Herpratiwi, Herpratiwi; Azizah, Alif Luthvi; Datania, Vivien; Yudhistira, Ardhi; Fadhilah, Tiara (Didaktika, 2023)
This research was carried out with the aim of analyzing the effect of applying the Treffinger learning model on students' higher order thinking skills (HOTS). In fact, low higher order thinking skills (HOTS) of students is a form of applying an appropriate learning model.  Whereas HOTS is one of the abilities that must be possessed by students in the 21st century. Treffinger learning model is suitable to be applied because it is based on the development of the times. The research method used is quantitative research and pre-experimental design. The population in this study were 115 and the sample used is 26 students in class V of elementary school. The sampling technique used was cluster sampling. Data collection techniques using tests and documentation. Hypothesis test using t test. Based on the results of this study, there is a significant effect from the application of the Treffinger learning model on the higher order thinking skills grade students at SD Negeri 1 Triharjo, which is indicated by a significance value of 0.000 (p = 0.05). The Treffinger learning model makes students more active in the learning process and causes changes in behavior in accordance with learning objectives. The Treffinger learning model is expected to be an alternative that educators can use in increasing student HOTS.